2019
DOI: 10.3390/app9071480
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Fiber Surface Plasmon Resonance Sensor for High-Sensitive Mercury Ion Detection

Abstract: This paper proposes a reflective fiber mercury ion sensor based on the surface plasmon resonance (SPR) principle and chitosan (CS)/polyacrylic acid (PAA) multilayer sensitive film. By optimizing the coating parameters of the gold film, the refractive index (RI) sensitivity of the reflective SPR sensor is demonstrated to be 2110.33 nm/RIU. Then, a multi-layer CS/PAA film is fixed on the surface of the gold film as a mercury ion sensitive film to form a reflective SPR fiber mercury ion sensor. Experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The most toxic chemical forms of Hg are ionic Hg (Hg 2+ ), causes serious damage to human health such as brain damage, immune dysfunction and paralysis [ 24 , 25 , 26 ]. Therefore, the removal and detection of Hg 2+ in the aqueous environment are of great significance [ 27 , 28 , 29 , 30 , 31 ]. Among the existing optical techniques to detect Hg 2+ are colorimetric, fluorescent, chemosensor, electrochemiluminescence (ECL) and photoluminescent (PL) [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most toxic chemical forms of Hg are ionic Hg (Hg 2+ ), causes serious damage to human health such as brain damage, immune dysfunction and paralysis [ 24 , 25 , 26 ]. Therefore, the removal and detection of Hg 2+ in the aqueous environment are of great significance [ 27 , 28 , 29 , 30 , 31 ]. Among the existing optical techniques to detect Hg 2+ are colorimetric, fluorescent, chemosensor, electrochemiluminescence (ECL) and photoluminescent (PL) [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depend on the same system in Kretschmann prism that associated, the SPR with fiber optic technology owns great improvements with giving advantages exceeding the common prism based SPR reaches, such as a low cost, miniaturization, and simplicity [5]. SPR fiber sensors can operate in the reflection mode (fiber tip), a sensor consisting of the fiber with a perfect cleave and a layer of gold or another plasmonic material at one end of the fiber, which reflects light towards the detector at the opposite end [6].…”
Section: Figure 1 Kretschmann Spr Configurationmentioning
confidence: 99%
“…There are two forms of the SPR methods detection according to the resonance coupling condition given by equation ( 6) [11]: (6) dielectric function of the prism, is incident angle.…”
Section: … (5)mentioning
confidence: 99%
“…The fiber-optic SPR sensor has already been used for Hg 2+ detection: Raj et al reported using a fiber-optic SPR sensor for Hg 2+ ion detection by utilizing an Au NPs–polyvinyl alcohol (PVA) hybrid as a sensing material, however, the limit of detection (LOD) was only down to 1 × 10 −6 M [ 24 ]. Taking advantage of a chitosan (CS)/polyacrylic acid (PAA) multilayer as the sensitive film, Chen et al demonstrated that the detection sensitivity of a fiber-optic SPR Hg 2+ ion sensor was up to 0.5586 nm/μM [ 25 ].…”
Section: Introductionmentioning
confidence: 99%